Companies Determinants Of Income Smoothing: Empirical Study Of Property, Real Estate, And Building Construction Sectors Before And In The Time Of Covid 19 - Olivia, Olivia; Suryaningsih, Rosita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
This research aims to obtain empirical evidence regarding the effect of financial leverage, profitability, cash holding, and firm value towards income smoothing. Income smoothing is a company’s effort to make earnings less volatile significantly. Stable earnings can be used as a basis for decision-making by stakeholders, while for the company itself, it’s useful for maintaining business continuity and management performance. The object of this research is all companies in the property, real estate, and building construction sector listed on Indonesia Stock Exchange for the 2016-2021 period. Research samples were taken using a purposive sampling method. Secondary data was used in the form of financial reports and stock price information to be tested using the multiple linear regression method. The results of this research are (1) financial leverage has no effect towards income smoothing, (2) profitability has a significant negative effect towards income smoothing, (3) cash holding has no negative effect towards income smoothing, (4) firm value has a significant positive effect towards income smoothing. Financial leverage, profitability, cash holding, and firm value simultaneously have a significant effect towards income smoothing